Paradigma Kepemimpinan Reflektif Sebagai Strategi Penguatan Nilai Moral dan Etika dalam Pendidikan Sekolah Dasar Formal - Amin Harahap; Eka Aprilla Harahap; Octa Olivia Putri; Dewi Sukowati (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Character development in primary education is closely linked to the internalization of moral and ethical values, which remains a challenge in formal schools due to variations in educational leadership quality. This study aims to examine reflective leadership as a strategic approach to strengthening moral and ethical values in primary education through a case study conducted at MIS Al Ikhlas Kampung Dalam. Using a qualitative descriptive design, data were collected through classroom observations, in-depth interviews with the principal and teachers, and analysis of school policy documents and activities. Data analysis involved reduction, presentation, and conclusion drawing, supported by source and technique triangulation to ensure validity. The findings reveal that reflective leadership is demonstrated through continuous policy evaluation, openness to feedback, and ethically grounded decision-making. This leadership approach fosters a positive moral school culture and supports students’ character formation through role modeling and value internalization in everyday school practices.